The Impact of Turbulence on Physics of the Geomagnetic Tail - Antonova, Elizaveta E.; Stepanova, Marina V. (Frontiers in Astronomy and Space Sciences, 2021)
There is a vast amount of evidence that suggests that the geomagnetic tail is like a turbulent wake behind an obstacle. Large-scale vortices in the wake are able to generate turbulent transport that takes place both along the plasma sheet, in the X and Y directions, and across the plasma sheet, in the Z direction. Thus, turbulent fluctuations in all directions should be taken into consideration when analyzing plasma transport in the plasma sheet, and stability of the plasma sheet configurations. In this review, we summarize and discuss the main results of large and middle scale magnetospheric turbulence yielded by data analysis and modelling. We also identify changes in the description of the magnetospheric dynamics connected with the existence of turbulent fluctuations in the tail.